Variety of Development Chinese Automakers in Market Reform and Globalization - Feng, Qiushi (Springer Singapore, 2018)
This book examines China, the world's largest auto market since 2008 and the story of how Chinese auto-makers developed is the story of the Chinese economy in microcosm. It focuses on China's systemically important automobile sector, this book reveals how local institutions have moderated structural changes at national and global levels, and consequently generated significant organizational diversity in the production sphere. This book begins with the intriguing observation that individual Chinese car makers have been evolving in different directions despite a shared context; what factors led to these diverse choices and positioning? It is the central aim of this book to explain the variety of institutional forms used by Chinese car manufacturers in navigating the market transition and answering the challenges posed by globalization. .